The role of energy in a real-business-cycle model with an endogenous capital utilization rate and a government sector: lessons from Bulgaria (1999-2016) - Aleksandar Vasilev (Central European Economic Journal, 2019)
We introduce a pro-cyclical endogenous utilization rate of physical capita1 stock into a real-business-cycle model augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of the endogenous depreciation rate, and the capital utilization mechanism working through the use of energy for cyclical fluctuations in Bulgaria. In particular, a positive shock to energy prices in the model works like a negative technological shock. Allowing for variations in factor utilization and the presence of energy as a factor of production improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework with constant depreciation and a fixed utilization rate of physical capital, e.g., Vasilev (2009)
Keywords: E32; E22; E27; 330; Business fluctuations; capital utilization rate; endogenous depreciation rate; energy use; energy prices; Bulgaria